Environmental harshness and unpredictability, life history, and social and academic behavior of adolescents in nine countries - Lei Chang (2019)
© 2018 American Psychological Association. Safety is essential for life. To survive, humans and other animals have developed sets of psychological and physiological adaptations known as life history (LH) tradeoff strategies in response to various safety constraints. Evolutionarily selected LH strategies in turn regulate development and behavior to optimize survival under prevailing safety conditions. The present study tested LH hypotheses concerning safety based on a 6-year longitudinal sample of 1,245 adolescents and their parents from 9 countries. The results revealed that, invariant across countries, environmental harshness, and unpredictability (lack of safety) was negatively associated with slow LH behavioral profile, measured 2 years later, and slow LH behavioral profile was negatively and positively associated with externalizing behavior and academic performance, respectively, as measured an additional 2 years later. These results support the evolutionary conception that human development responds to environmental safety cues through LH regulation of social and learning behaviors.